Business Process Management in Hotels: With a Focus on Delivering Quality Guest Service - Ozdemir, Ali Ihsan; Çolak, Abdullah; Shmilli, Jerina (Springer Netherlands rbk@louisiana.edu, 2018)
In this study business process management as a tool of improvement service quality is introduced and it is examined that how it can be used to improve service quality in hotel sector. It is assumed that re-engineering of the business processes in hotel may contribute to optimize the operational processes and service by focusing on guest service. All the interactions and transactions between the guest and the hotel during her/his stay, determine the type and nature of front office operations. The stages of guest stay are: (a) pre-arrival, (b) arrival and accommodation, (c) stay, and (d) departure. Each steps are analyzed and business process improvements are applied by case study approach in a hotel which is one of the biggest hotel in Tirana, Albania. As a result of this study valuable recommendations are developed to enhance guest service quality. © 2019 Elsevier B.V., All rights reserved.
Keywords: Albania; Business Process Management; Guest Service; Hospitality Sector; Hotel Sector